A controlled double blind study of azathioprine in the management of Crohn's disease. Issue 5 (November 1995) - Candy, S; Wright, J; Gerber, M; Adams, G; Gerig, M; Goodman, R
Abstract : While immunosuppressive agents are used widely in the management of Crohn's disease, their efficacy has not been well established in randomised controlled trials. This study was designed to examine whether azathioprine increases remission rate when used in conjunction with a diminishing dose regimen of prednisolone over a period of 12 weeks. It further examined whether azathioprine offers any therapeutic advantage over placebo in the maintenance of remission in Crohn's disease over a period of 15 months. Sixty three patients with active Crohn's disease were treated with a 12 weeks diminishing dose of prednisolone and at the same time entered into a randomised, double blind 15 month trial of either azathioprine (2.5 mg/kg) or placebo. Remission rates between the two groups were compared at 12 weeks and at 15 months. There was no significant difference in the proportion of patients who had achieved and maintained remission by week 12 but at 15 months there was a highly significant difference in the proportion of patients in remission (42% receiving azathioprine v 7% receiving placebo), p = 0.001. Using life tables this beneficial effect was reflected as the difference in the median number of days on the trial (p = 0.02). There were significantly greater decreases over the trial period in the median erythrocyte sedimentation rate, C reactive protein, and leucocyte count in the azathioprine group. There were no cases of severe bone marrow suppression or clinical pancreatitis. In conclusion, azathioprine offers a therapeutic advantage over placebo in the maintenance of remission in Crohn's disease.